"Rzodkiewki" Janusza Morgensterna - Hendrykowski, Marek (Images. The International Journal of European Film, Performing Arts and Audiovisual Communication, 2012)
Janusz Morgenstern’s „Radishes” Marek Hendrykowski’s essay presents the importance of Janusz Morgenstern’s early short film Radishes made after Stalin’s death, in 1954 as a student work produced by Film School in Łódź. The main character, old worker Gruliński loses his clear hopes and human illusions. The pesimistic conclusion is closed further by the simultaneous description of the hero’s social image within a discourse of origins and the sacred which evacuates analysis of class conflict and sociological approach in the narrative of an “ordinary good man” brutally disturbed in his desires and works by the irruption and power of an omnipotent destructive stalinist “red tape” bureaucracy. The poetics of Radishes is deeply influenced by the style of an Italian neorealism, first of all by its famous masterpiece, Vittorio De Sica’s Umberto D. (1952).